Integration of knowledge in theory and practice: the contribution of Bediuzzaman Said Nuri - Ali, Md. Yousuf (Bangladesh Institute of Islamic Thought (BIIT), 2011)
Integration of knowledge in Islam is an intellectual and epistemological challenge. Indeed the first revelation of the Qur‟an is “to read and write”1 and the Prophet Muhammad continued its process until the revelation of the whole Qur‟an was completed. Muslim scholars and thinkers espoused to develop man‟s intellectual efforts in the various ages.2 The integration process of knowledge was revived in the twentieth century by several scholars and thinkers, Bediuzzaman Said Nursi (1877-1960) being one of them. This approach argues that without integration of knowledge between religious sciences and modern sciences in accordance with the need of time, progress and development in the Muslim world is not possible. Such an approach is particularly compelling because it can eschew the accusation that Western values are being imposed upon Islam. Muslim scholars who proposed the process of integration have faced resistance from traditionalists. The accusation is that they are not loyal to Islam and deny its heritage. However, one of the highly influential intellectuals and reformers, Bediuzzaman Said Nursi greatly contributed to understanding the reformation of society and the necessity of the integration of knowledge. Many Islamic thinkers and activists were influenced all over the world by his intellectual effort. His ideas took shape in Turkey in influencing contemporary intellectuals. However, although he is well known for his scholarship and reformist work, his efforts at integration of knowledge3 have not received the scholarly attention they deserved. This article focuses on how Bediuzzaman Said Nuri employed the process of integration of knowledge to combine the religious sciences and modern sciences in a way that does not condone the contradiction. It examines the theoretical dimensions and practical application of the process of integration of knowledge. It also explores whether this approach can implement in reality or whether the only option for scholars who proposed this project is to discuss its theoretical dimension.